Butterfly community structure and floral visitation in Sukamade, Meru Betiri National Park, Indonesia - ABDU ROHMAN; DIMAS AMIRUL HASAN; WACHJU SUBCHAN; DENI PRABOWO (Society for Indonesian Biodiversity, 2026)
Abstract. Rohman A, Hasan DA, Subchan W, Prabowo D. 2026. Butterfly community structure and floral visitation in Sukamade, Meru Betiri National Park, Indonesia. Biodiversitas 27 (5): d270506. https://doi.org/10.13057/biodiv/d270506. This study investigates the community structure of butterflies (Lepidoptera: Papilionoidea) and their associated floral resources in the Sukamade Resort area of Meru Betiri National Park, Indonesia, a crucial conservation area for protected species. The objective was to evaluate how butterfly diversity, species richness, and community composition vary across habitat types and their relationships with vegetation composition and abiotic factors. Butterflies were surveyed using the cruising method along 100 m × 10 m transects across 12 sampling sites representing four habitat types. A total of 423 butterfly individuals representing 26 species from four families were recorded, with Ypthima horsfieldii being the most abundant, and the protected Troides helena also present. Open Land showed the highest diversity (H' = 2.72) and species richness (Margalef Index = 4.67). The Dominance Index was highest in Coastal Forest (0.17), while the Closed-canopy Forest recorded the highest species evenness (0.84). A total of 39 plant species were recorded, with the white-flowered Chromolaena odorata showing the highest number of butterfly visits, involving 12 species. Multivariate analyses (Canonical Correspondence Analysis (CCA) and Principal Component Analysis (PCA)) were applied to examine patterns of butterfly distribution in relation to abiotic factors and vegetation composition. These analyses were exploratory and revealed general patterns of association. These findings contribute important ecological information for conservation management and highlight the ecological significance of habitat heterogeneity in supporting butterfly diversity within the park.